Bromelain production: Current trends and perspective - Bala, Muntari; Ismail, Nurul Azira; Mel, Maizirwan; Jami, Mohammed Saedi; Salleh, Hamzah Mohd.; Amid, Azura (Museum Hist Naturelle, 2012)
Bromelain is a mixture of proteolytic enzymes derived from the stems and juice of pineapples. It has been extensively used in food industry; for meat tenderization, baking processes, and in prevention of browning of apple juice. Stem bromelain is a highly accepted phytotherapeutic agent. It has anti-tumor and antiinflammatory effects, use in wound healing, as digestive aids, etc. This review aims at presenting a detailed account on the level of achievement on bromelain production from the conventional methods. Specifically, the isolation, purification and the biochemical properties of bromelain are discussed. The study also focused on the current trends and the progress made in the production of recombinant stem bromelain in Escherichia coli. This involved cloning of stem bromelain gene and its expression, optimization of labscale fermentation conditions for E. coli harboring recombinant bromelain as well as the enzyme thermal and storage stability measured using differential scanning calorimetry. It is hoped that this review would provide relevant information to contemporary researchers who are active in the field of bromelain and other related proteases.